Test on the Reliability of the Subsurface Fault Geometry Estimated by Deformed River Terraces Along the Bailang River, North Front of the Qilian Shan (North West China) - Hu, Xiaofei; Ji, Xianghe; Cao, Xilin; Chen, Jiuying; Pan, Baotian (Frontiers in Earth Science, 2021)
The subsurface fault geometry is the base to understand the process of crust deformation and mountain building. Based on kinematic models for fault-related folds, the geomorphic method is applied recently to estimate the subsurface fault geometry, while the validation on its reliability is lack. In this study, we surveyed a suit of river terrace surfaces across an active fold at the north front of the Qilian Shan. According to the deformation geometry of the terraces, the fold deformation is interpreted by the listric-fault fold model, and based on this kinematic model, the fault geometry underlying the fold is estimated. In comparing between the estimated fault geometry and the seismic reflection profile, we found that the decollement depth and the back thrust are highly consistent with each other. Although some small fault bends or internal shearing cannot be estimated solely by the terrace deformation, the overall fault geometry is successfully revealed by the terrace deformation. Using this fault geometry and terrace dating results, the region deformation kinematics is re-evaluated, which suggests that the dip slip (in a rate 1.8 ±0.4 mm/a) along the decollement is mainly accommodated by two structures, one is the blind back-thrust fault within the piggy-basin in a dip slip rate of 0.9 ±0.3 mm/a and another is the thrust and fold at the west portion of the Yumu Shan range.